Induction of heme oxygenase alleviates skeletal muscle atrophy in mice by inhibiting the activation of NLRP3 inflammasome REN Chunguang1, PU Rongxi2, HU Die2, ZHANG Yalian1, CAI Xing1, SHU Bin1, YANG Zhong2 - REN Chunguang; PU Rongxi; HU Die; ZHANG Yalian; CAI Xing; SHU Bin; YANG Zhong (Di-san junyi daxue xuebao, 2022)
Objective To investigate whether induction of heme oxygenase-1 (HO-1) can reduce skeletal muscle atrophy in mice by inhibiting the activation of NLRP3 inflammasome. Methods Thirty-two 8-week-old male C57BL/6 mice were randomly divided into normal group, model group (the model of lower limb muscular atrophy was established by tail suspension), heme chloride group (HO-1 expression was induced by intraperitoneal injection of hemin in the model mice), and zinc protoporphyrin group (on the basis of hemin chloride group, ZnPP was injected intraperitoneally to antagonize HO-1 expression), with 8 mice in each group. Another 8 mice at the same age were injected with lentivirus into tibialis anterior muscle and the model of lower limb muscle atrophy was established simultaneously, with the left side as lentivirus intervention subgroup (injection of lentiviral vector of NLRP3 RNAi to inhibit the expression of NLRP3), and the right side as lentivirus control subgroup (injection of blank lentiviral vector). The changes of muscle volume were observed by HE staining and muscle/body weight ratio. The protein levels of NLRP3, ASC and Caspase-1 in the tibialis anterior muscle were determined by Western blotting. The levels of IL-1β and IL-18 and oxidative stress molecules in the muscle tissues were determined by ELISA. Results The typical mouse model of lower extremity muscular atrophy was successfully established by tail suspension. HO-1 induction resulted in significantly reduced muscular atrophy and decreased expression of NLRP3 inflammasome related proteins ASC and Caspase-1 in the heme chloride group when compared with the model group (P < 0.05). There were no significant differences in the protein levels of above 2 molecules between the zinc protoporphyrin group and the model group. Knockdown of NLRP3 by lentiviral vector led to significantly reduced muscle atrophy, decreased expression of NLRP3 inflammasome related proteins (P < 0.05), and lower levels of downstream proteins IL-1 β and IL-18 (P < 0.05) when compared with the lentivirus control subgroup; The oxidative stress of muscle tissue was alleviated (P < 0.05). Conclusion Induction of HO-1 can reduce skeletal muscle atrophy in tail suspension mice by inhibiting the activation of NLRP3 inflammasome.